Characteristics of p.Gln368Ter Myocilin Variant and Influence of Polygenic Risk on Glaucoma Penetrance in the UK Biobank. - Zebardast, Nazlee; Sekimitsu, Sayuri; Wang, Jiali; Elze, Tobias; Gharahkhani, Puya; Cole, Brian S.; Lin, Michael M.; Segre, Ayellet V.; Wiggs, Janey L. (Ophthalmology, 2021)
PURPOSE: MYOC (myocilin) mutations account for 3% to 5% of primary open-angle glaucoma (POAG) cases. We aimed to understand the true population-wide penetrance and characteristics of glaucoma among individuals with the most common MYOC variant (p.Gln368Ter) and the impact of a POAG polygenic risk score (PRS) in this population. DESIGN: Cross-sectional population-based study. PARTICIPANTS: Individuals with the p.Gln368Ter variant among 77 959 UK Biobank participants with fundus photographs (FPs). METHODS: A genome-wide POAG PRS was computed, and 2 masked graders reviewed FPs for disc-defined glaucoma (DDG). MAIN OUTCOME MEASURES: Penetrance of glaucoma. RESULTS: Two hundred individuals carried the p.Gln368Ter heterozygous genotype, and 177 had gradable FPs. One hundred thirty-two showed no evidence of glaucoma, 45 (25.4%) had probable/definite glaucoma in at least 1 eye, and 19 (10.7%) had bilateral glaucoma. No differences were found in age, race/ethnicity, or gender among groups (P > 0.05). Of those with DDG, 31% self-reported or had International Classification of Diseases codes for glaucoma, whereas 69% were undiagnosed. Those with DDG had higher medication-adjusted cornea-corrected intraocular pressure (IOPcc) (P < 0.001) vs. those without glaucoma. This difference in IOPcc was larger in those with DDG with a prior glaucoma diagnosis versus those not diagnosed (P < 0.001). Most p.Gln368Ter carriers showed IOP in the normal range (≤21 mmHg), although this proportion was lower in those with DDG (P < 0.02) and those with prior glaucoma diagnosis (P < 0.03). Prevalence of DDG increased with each decile of POAG PRS. Individuals with DDG demonstrated significantly higher PRS compared with those without glaucoma (0.37 ± 0.97 vs. 0.01 ± 0.90; P = 0.03). Of those with DDG, individuals with a prior diagnosis of glaucoma had higher PRS compared with undiagnosed individuals (1.31 ± 0.64 vs. 0.00 ± 0.81; P < 0.001) and 27.5 times (95% confidence interval, 2.5-306.6) adjusted odds of being in the top decile of PRS for POAG. CONCLUSIONS: One in 4 individuals with the MYOC p.Gln368Ter mutation demonstrated evidence of glaucoma, a substantially higher penetrance than previously estimated, with 69% of cases undetected. A large portion of p.Gln368Ter carriers, including those with DDG, have IOP in the normal range, despite similar age. Polygenic risk score increases disease penetrance and severity, supporting the usefulness of PRS in risk stratification among MYOC p.Gln368Ter carriers.
EVALuna2:474010